Assessment of Endothelial Cell Count Changes Post-Yttrium Aluminium Garnet Laser for Posterior Capsular Opacification - Khan, Amna; Abdul Rauf; Muhammad Haroon Sarfraz; Summaya Khan; Taimoor Ashraf; Nazia Iqbal (Pakistan Armed Forces Medical Journal, 2023)
Objective: The study aimed to assess the effect of Neodymium : Yttrium Aluminium Garnet laser (ND:YAG laser) on endothelial cell count loss and anterior segment elements. Study Design: Quasi-experimental. Place and Duration Of Study: Armed Forces Institute of Ophthalmology, Rawalpindi from Jul 2021 to Feb 2022. Methodology: A total of 60 patients with a history of posterior capsular opacities planned for Neodymium: Yttrium Aluminium Garnet laser posterior capsulotomy were included. Specular microscopy was done pre and post-laser to study and parameters such as central corneal thickness, endothelial cell count, intra-ocular pressure was noted. Data were analyzed by using the Statistical Package for the Social Sciences version 23 software Result: After four weeks of Neodymium : Yttrium Aluminium Garnet laser, there was no significant change in the intraocular pressure (p=0.334), however, the visual acuity improved from 0.6±0.3-0.05±0.1 (p<0.001) along with a decrease in endothelial cell count 2101±485-1919±427 (p<0.001) and central corneal thickness 0.504±0.03-0.502± 0.03 (p=0.010). A similar trend of changes in the parameters was observed for lower (1.0-1.2MJ) and higher energy (2.1-2.5MJ) in the sample for posterior capsulotomy. Conclusion: Our study concluded that the corneal structural changes occur post-Neodymium: Yttrium Aluminium Garnet posterior capsulotomy, including changes in endothelial cell count. However, there is no significant disturbance in the intraocular pressure after the procedure.